Effect of Removing Seminal Plasma Using a Sperm Filter on the Viability of Refrigerated Stallion Semen - Neto, Carlos Ramires [UNESP]; Monteiro, Grabriel Augusto [UNESP]; Soares, Rafaela Fatima [UNESP]; Pedrazzi, Cesar; Dell'aqua Junior, José Antônio [UNESP]; Papa, Frederico Ozanam [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2013)
Cooling of equine semen obtained from some stallions results in lower seminal quality and viability when the seminal plasma (SP) is present. The objective of this study was to evaluate the effect of the removal of SP using a Sperm Filter on the viability of cooled stallion semen. For this purpose, 31 stallions were used. Their ejaculates were divided into three groups: CN, semen was diluted with an extender; FLT, SP was removed by filtration; and CT, SP was removed by centrifugation and cooled to 15°C for 24 hours. Sperm kinetics and plasma membrane integrity were evaluated immediately after collection (T0) and after 24 hours of refrigeration (T1). No difference (P > .05) was noted at T1 for total sperm motility (TM), progressive sperm motility, or plasma membrane integrity when semen samples from all the stallions were analyzed. However, when samples from stallions termed bad coolers were analyzed (TM = <30% at T1), a difference was observed in TM and progressive sperm motility for CN compared with FLT and CT at T1. Sperm recovery was greater when SP was removed using the filter (FLT) to that when the SP was removed by centrifugation (CN) (89% vs. 81%). Thus, we concluded that filtering with a Sperm Filter is an efficient and practical method for removal of SP from stallion ejaculates, with lower sperm loss than centrifugation. We also found that the presence of SP reduces the quality and viability of cooled semen from stallions whose semen is sensitive to the process of refrigeration. © 2013 Elsevier Inc.
Keywords: Centrifugation; Cooled semen; Seminal plasma; Sperm filter; Stallion; Equidae